UMPSA celebrates first batch of rail industry dual-degree graduates - T.N., Alagesh (New Straits Times Press (M) Bhd., 2025)
KUANTAN: Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) reached another milestone today, producing its first batch of dual-degree scholars in the rail industry, specialising in civil, mechanical and electrical engineering fields.